2018
DOI: 10.11114/jets.v6i12.3624
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Out-of-School Learning Environments on 6th Grade Secondary School Students Attitude Towards Science Course

Abstract: This study was conducted for the purpose of determining the impacts of out-of-school learning environments on 6th-grade students’ attitudes towards science course. In the study, the quasi-experimental model and pretest-posttest control grouped experimental design was employed. The experimental process step of the study was carried out on 6th-grade students who receive education in a secondary school in Turkey in 2017 and maintained for 18 weeks. 60 students are included in the study group of the research (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…The classroom environment has also been reported as a significant predictor of science (Anwer et al, 2012;Montes et al, 2018;Ngila & Makewa, 2014;Oh & Yager, 2004;Yildirim, 2018). This was revealed in six studies, with two showing no impact (Montes et al, 2018;Ngila & Makewa, 2014).…”
Section: Classroom Environmentmentioning
confidence: 94%
See 2 more Smart Citations
“…The classroom environment has also been reported as a significant predictor of science (Anwer et al, 2012;Montes et al, 2018;Ngila & Makewa, 2014;Oh & Yager, 2004;Yildirim, 2018). This was revealed in six studies, with two showing no impact (Montes et al, 2018;Ngila & Makewa, 2014).…”
Section: Classroom Environmentmentioning
confidence: 94%
“…Yes (+) (Yildirim, 2018) There was a meaningful difference between students exposed to out of school learning environment and those not exposed to the same environment (p = 0.001, p < 0.05).…”
Section: Yes (+)mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering studies in the related literature, studies that examine the effects of out-of-class teaching activities on cognitive objectives with experimental methods outnumbered (Şahin & Sağlamer Yazgan, 2013;Bozdoğan & Kavcı, 2016;Bodur & Yıldırım, 2018;Borsos, Borić, & Patocskai, 2018;Durel, 2018;Sontay & Karamustafaoğlu, 2018;Avcı & Gümüş, 2020). However, some studies reported that out-of-class activities positively affect objectives in the affective field, which is indeed difficult to observe (Doğan, Çiçek, & Saraç, 2017;Yavuz Topaloğlu & Balkan Kıyıcı, 2018;Yıldırım, 2018). Out-of-class learning processes, which are an important part of contemporary education, can include activities lasting from a few minutes to days (Donaldson & Goering, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of normality scientists describe how students perceive scientists in the field of science. Attitudes of scientists in solving problems and finding new discoveries that can be used as role models for students [25]. Since student scientists are identical to people who work in the laboratory and have new findings.…”
Section: Introductionmentioning
confidence: 99%